Comparative study between the lean manufacturing versus the cleaner production - Pereira, Ricardo; Hatakeyama, Kazuo; Hurtado, Ana Lúcia Berretta (International Journal of Advanced Engineering Research and Science, 2023)
Cost reduction, making the most of resources, whether raw materials, machines or labor, are a great challenge for organizations and their managers, which occasionally in day-to-day life do not always have their full utilization. In addition to these, there are efforts to search for increasingly ecologically correct processes and products. Coming to common sense and delivering a quality product, on time and that generates the least amount of waste and impact on the environment is the current challenge. The article shows two systems, lean manufacturing and its tools to help reduce waste, and Cleaner Production, which seeks to optimize resources in favor of the lowest impact to be generated. In addition to these, it aims to show the benefits generated by them when applied correctly. The article was developed through qualitative research, with searches carried out for case studies and articles, through exploratory and bibliographical research. Lean Manufacturing aims to highlight and eliminate all waste, whether in the productive area or in the administrative area, Cleaner Production aims to identify the generation of impacts and highlight them in the search for the elimination of generation. As a result, there is a similarity between both methodologies, but with different focuses, one more structured with defined methodologies and analysis and implementation tools, the other with step-by-step implementation, but somewhat superficial.